In a 32-Year-Old Woman With Chronic Neck Pain and Headaches, Will an Exercise Regimen Be Beneficial for Reducing Her Reports of Neck Pain and Headaches? - Mintken, Paul E.; Cleland, Joshua (Physical Therapy, 2012)
<LEAP> highlights the findings and application of Cochrane reviews and other evidence pertinent to the practice of physical therapy. The Cochrane Library is a respected source of reliable evidence related to health care. Cochrane systematic reviews explore the evidence for and against the effectiveness and appropriateness of interventions-medications, surgery, education, nutrition, exercise-and the evidence for and against the use of diagnostic tests for specific conditions. Cochrane reviews are designed to facilitate the decisions of clinicians, patients, and others in health care by providing a careful review and interpretation of research studies published in the scientific literature.1 Each article in this PTJ series summarizes a Cochrane review or other scientific evidence on a single topic and presents clinical scenarios based on real patients or programs to illustrate how the results of the review can be used to directly inform clinical decisions. This article focuses on a 32-year-old woman with chronic neck pain with headaches. Could an exercise program help reduce her neck pain and headaches?